PENGARUH PENGETAHUAN AKSEPTOR KB TENTANG COVID-19 DENGAN KEPATUHAN JADWALKUNJUNGAN KONTRASESPSI - Selvy Apriani; Ria Gustirini (LPPM STIKes Mitra Adiguna, 2022)
Abstract The Corona virus can spread from person to person through droplets that come out of the nose or mouth. The impact of the spread of the Covid-19 outbreak in Indonesia affects various aspects, including the Family Planning Program service. The Head of BKKBN acknowledged that there was a decrease in family planning participants in March 2020 when compared to February 2020. From the data obtained, the use of IUDs in February 2020 decreased to 23,383, while implants from 81,062 to 51,536, injections from 524,989 to 341,109, pills 251,619 to 146,767 , condoms from 31,502 to 19,583, MOP from 2,283 to 1,196, and MOW from 13,571 to 8,093. This decrease in the number of family planning participants can encourage a baby boom. The purpose of this study was to determine whether there was an effect of family planning acceptors' knowledge about Covid-19 with adherence to the contraceptive visit schedule. The research methodology used in this study used a quantitative approach, with the correlation quantitative method. Data collection techniques in this study using a questionnaire and data analysis using Chi Square Test. The results of the study obtained that the knowledge of family planning acceptors about Covid-19 prevention was still low, decreased compliance with family planning acceptor visits during the pandemic and there was an influence of knowledge of family planning acceptors about Covid-19 with adherence to the contraceptive visit schedule with a p-value = 0.002. Suggestions It is recommended for family planning acceptors to be able to increase their knowledge about covid-19. Keywords: Covid-19, family planning, family planning compliance, family planning visits